DIVERSITY OF INSECTS IN THE PADDY FIELDS OF MUNDAKAM VAYAL, KANNUR DISTRICT - MATHEW, VINNI; LIVINGSTONE, ANANTHI RACHEL (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
This study was conducted to determine the variation in the population of insects in the paddy plots of Mundakam Vayal area, Nedungome village, Kannur district. In this study a total of 71 insect species were observed. Out of these species, 52 species under eight orders were identified. Lepidoptera (12), Odonata (10), and Coleoptera (9) were recorded as the most dominant orders, followed by Araneae (7), Hemiptera (6), Orthoptera (5), Hymenoptera (2), and Diptera (1). The highest population density was in Lepidoptera, and the highest species diversity was seen in both Lepidoptera and Coleoptera. The most abundant species recorded were Cnaphalocrocis medinalis, belonging to the Order Lepidoptera, and Leptocorisa oratoria belonging to the order Hemiptera. The overall insect diversity and richness increased during the flowering and milky phase of the paddy plant. Results indicate that diversity of insects in paddy fields ensured a good balance between the populations of pests, and the beneficial insects (predators and parasitoids) of paddy. The diversity of insects can potentially be an effective way to conserve, use and enhance biodiversity to sustain food security in the agricultural ecosystem in the Mundakam Vayal area.